Functionalized graphene oxide triggers cell cycle checkpoint control through both the ATM and the ATR signaling pathways. (April 2018) - Wang, Yonghui; Xu, Jun; Xu, Ligeng; Tan, Xiaofang; Feng, Liangzhu; Luo, Yinchan; Liu, Jian; Liu, Zhuang; Peng, Rui
Abstract: How graphene oxide (GO) derivatives might affect the cell cycle has been rarely studied. Herein, a GO derivative was fabricated by functionalization of GO with polyethylene glycol (PEG) and polyethylenimine (PEI), and its cytotoxic mechanism was investigated in-depth. It was found that our obtained GO-PEG-PEI nanosheets, not the cytotoxic coating polymer PEI, could induce defect in S phase of the mammalian cell cycle, resulting in decreased DNA synthesis, S phase arrest, and abnormal cytoskeleton structure. Further analysis demonstrated that this damaging effect on S phase could be detected in all five tested mammalian cell lines. Even at seemingly safe concentration (∼90% cells viable), GO-PEG-PEI could still induce S phase defect. Detailed investigations revealed that GO-PEG-PEI could cause genomic DNA damage, activating the intra-S-phase checkpoint control via both the ATM and the ATR signaling pathways. Our work unveils the signaling pathways involved in the interaction of GO-PEG-PEI with mammalian cells, and highlights the necessity and importance of comprehensive investigations of the effects of nanomaterials on cellular pathways, such as the cell cycle in this case, even for those with seemingly little/low cytotoxicity during preliminary evaluations. Our work also highlights the critical roles of surface chemistry in biological effects of nanomaterials. Graphical abstract: Image 1